Performance evaluation of an all-fiber image-reject homodyne coherent Doppler wind lidar - C. F. Abari; A. T. Pedersen; E. Dellwik; J. Mann (Atmospheric Measurement Techniques, 2015)
The main purpose of this study is to evaluate the near-zero wind velocity measurement performance of two separate 1.5 μm all-fiber coherent Doppler lidars (CDLs). The performance characterization is carried out through the presentation of the results from two separate atmospheric field campaigns. In one campaign, a recently developed continuous wave (CW) CDL benefiting from an image-reject front-end was deployed. The other campaign utilized a different CW CDL, benefiting from a heterodyne receiver with intermediate-frequency (IF) sampling. In both field campaigns the results are compared against a sonic anemometer, as the reference instrument. The measurements clearly show that the image-reject architecture results in more accurate measurements of radial wind velocities close to zero. Close-to-zero velocities are usually associated with the vertical component of the wind and are important to characterize.